Pharmacological characterization of a novel, potent, selective, and orally active fatty acid amide hydrolase inhibitor, PKM‐833 [(R)‐N‐(pyridazin‐3‐yl)‐4‐(7‐(trifluoromethyl)chroman‐4‐yl)piperazine‐1‐carboxamide] in rats: Potential for the treatment of inflammatory pain - Toshiya Endo; Takashi Takeuchi; Shunsuke Maehara (Wiley, 2020)
Abstract Recently, we identified a novel fatty acid amide hydrolase (FAAH) inhibitor, PKM‐833 [(R)‐N‐(pyridazin‐3‐yl)‐4‐(7‐(trifluoromethyl)chroman‐4‐yl)piperazine‐1‐carboxamide]. The aim of the present study is to characterize the pharmacological profile of PKM‐833 in vitro and in vivo. PKM‐833 showed potent inhibitory activities against human and rat FAAH with IC50 values of 8.8 and 10 nmol/L, respectively, 200‐fold more selectivity against other 137 molecular targets, and irreversible mode of action. In pharmacokinetic and pharmacodynamic studies, PKM‐833 showed excellent brain penetration and good oral bioavailability, and elevated anandamide (AEA) concentrations in the rat brain. These data indicate that PKM‐833 is a potent, selective, orally active, and brain‐penetrable FAAH inhibitor. In behavioral studies using rat models, PKM‐833 significantly attenuated formalin‐induced pain responses (3 mg/kg) and improved mechanical allodynia in complete freund's adjuvant (CFA)‐induced inflammatory pain (0.3‐3 mg/kg). On the other hand, PKM‐833 did not show the analgesic effects against mechanical allodynia in chronic constriction injury (CCI)‐induced neuropathic pain up to 30 mg/kg. Regarding side effects, PKM‐833 had no significant effects on catalepsy and motor coordination up to 30 mg/kg. These results indicate that PKM‐833 is a useful pharmacological agent that can be used to investigate the role of FAAH and may have therapeutic potential for the treatment of inflammatory pain without undesirable side effects.